Successful Pain Management in a Pregnant Woman with a Herniated Intervertebral Disc Using Ultrasound-Guided Epidural Steroid Injection: A Case Report - Lee, Gi Su; Nam, Seung Hyub; Shin, Soyoung; Bae, Jin-Gon (Perinatology (Online), 2024)
This case report aimed to describe successful pain management and maintenance of pregnancy in a woman with a herniated intervertebral disc using ultrasound-guided epidural steroid injections (US ESI). A 43-year-old pregnant woman at 23 weeks’ gestation presented with severe radiating pain extending from the hip to the thigh and calf. Magnetic resonance imaging revealed a herniated disc at the L5–S1 level with severe compromise of the thecal sac. Multiple rounds of US ESI were performed that reduced her pain from a numerical rating scale score of 9–10 to approximately 6. The patient underwent a cesarean section at 36 weeks and 6 days’ gestation. Following delivery, the patient underwent a discectomy and has since experienced no recurrence of pain or complications. Pregnant women with herniated intervertebral discs may experience severe radicular pain but have limited treatment options. This case demonstrates that US ESI can be beneficial when appropriate. KCI Citation Count: 0